Effect of Drought Stress on Growth of Soybean under Seedling Stage - Mishra, Sheshnath; Patidar, Durgesh (International Journal of Economic Plants, 2023)
The present study was conducted during September-October, 2022 at Greenhouse facility of Experimental Farm, Faculty of Agriculture Sciences, Mandsaur University, Mandsaur, Madhya Pradesh, India to identify drought tolerant genotypes. Total sixty genotypes were sown on dated 02/09/2022 by using polythene bags in completely randomized block design with four different water regimes and two replications in each set during month of September, 2022. Data were recorded for root-shoot parameters and relative leaf water content. Mean performance of root length showed that among 60 genotypes, thirty genotypes showed increased tap roots under severe water deficit conditions (0%). Under sever water stress condition (0%) highest root length was recorded of genotypes NRC138 (20.5 cm) followed by GW251 (18.15 cm) and RSC1107 (17.2 cm) respectively while lowest root length was noted in accession GW312 (3.4 cm) followed by NRC37 (5 cm) and NRC 142 (5.15 cm) respectively. Under0% water stress highest relative leaf water content was observed in genotype JS2034 (97.16%) followed by GW10 (93.47%) and GW159 (89.18%) whereas lowest was found in GW28 (20.96%) followed by GW100 (26.31%) and AGS25 (26.66%). On basis of mean data of root length, relative leaf water content, root shoot ratio by length and visual observation of plants, 11 genotypes were identified as drought tolerant and 19 genotypes were identified as medium tolerant. The identified drought tolerant genotypes may be used as water stress tolerant genotypes in future for improvement of crop in relation to drought tolerance.